Irische Komputistik zwischen Isidor von Sevilla und Beda Venerabilis: Ursprung, karolingische Rezeption und generelle Forschungsperspektiven - Warntjes, Immo (Viator (English and Multilingual Edition), 2011)
Abstract Computistical studies of the past centuries have primarily focused on the works of well-known individuals, while anonymous texts have been widely left unconsidered, leading to an immense overrating of the scientific achievements of the scholars known by name. Only within the past few years have the intellectual milieus that produced and influenced the known authors received some attention. This article defines on a textual basis Irish and Anglo-Saxon scientific milieus between Isidore of Seville and the Venerable Bede by providing a survey of all known computistical works of this period. On this basis, the Irish scientific contribution to the Carolingian educational and intellectual renaissance is assessed before the more general desiderata in the modern study of early medieval computistica are outlined at the end of this paper.